Henry II : a medieval soldier at war, 1147-1189 - Hosler, John D. (History of warfare ;, 2007)
There are no book-length studies in any language on the military career of King Henry II of England (1154-1189). Historians have generally regarded his warfare as cautious and limited, and the king himself, while noted for his considerable political and legal accomplishments, is not considered one of the great commanders of the Middle Ages. This book reexamines the medieval evidence and situates Henry II within the context of practiced warfare of the twelfth century. It sketches a narrative of his military activities from boyhood to death and examines his use of fortifications, manpower, strat.